Combined effects of buoyancy and electric forces on non-isothermal melting of a dielectric phase change material. (June 2022) - Selvakumar, R. Deepak; Vengadesan, S.
Abstract: Numerical investigations of non-isothermal melting of a dielectric PCM under the combined influence of buoyancy and electric forces have been performed. The coupled set of governing equations which include the Poisson equation for electric potential, Nernst–Planck equation for charge transport, Navier–Stokes equations and the energy equation are implemented in the finite-volume framework of OpenFOAM®. The solid–liquid phase change is modeled by an enthalpy source based approach and temperature dependent dielectric properties have been considered. The dynamic evolution of the electrohydrodynamics (EHD) assisted melting process is analyzed. In the presence of electric field, melting rate curve undergoes a deflection at a point that indicates the shift from natural convection dominated melting to electroconvection dominated melting. The EHD flow compliments the buoyancy driven flow, and the multiple smaller convective rolls of EHD flow enhances the mixing in liquid region. The melting time is a decreasing function of electric Rayleigh number T, whereas, the maximum melt fraction is an increasing function of T . Although the role of Rayleigh number R a is minimal at higher values of T, R a determines the occurrence of deflection point. The dielectric force induced by the temperature dependent dielectric properties does not have a significant influence on the melting process, for the parameters considered in this study. Highlights: Numerical analysis of EHD assisted melting process has been presented. Combined effects of buoyancy and electric forces have been analyzed. Temperature dependent dielectric properties have been considered. Buoyancy driven melting shifts to EHD dominated melting. Role of different parameters in EHD assisted melting have been discussed.